Identification of newly formed toxic chemicals in E-cigarette aerosols with Orbitrap mass spectrometry and implications on E-cigarette control. Issue 2 (August 2021) - Yan, Beizhan; Zagorevski, Dimitri; Ilievski, Vesna; Kleiman, Norman J; Re, Diane B; Navas-Acien, Ana; Hilpert, Markus
The increasing use of electronic nicotine delivery systems (ENDS) is of concern due to multiple emerging adverse health effects. Most analyses of the harmful chemicals of ENDS have targeted metals or carbonyls generated by thermal decomposition of carrier liquids such as propylene glycol. However, new complex compounds not routinely identified and with unknown health consequences could be formed. ENDS aerosol samples were collected by the direct aerosol droplet deposition method. Untargeted analysis was performed using Orbitrap mass spectrometry with high mass accuracy. We identified more than 30 "features" in the aerosol characterized by pairs of the mass-to-charge ratio " m / z " of the compound and the retention time. We identified several compounds containing nicotine and propylene glycol (NIC-PG), whose abundance relative to nicotine increased along with vaping power used. On the basis of the prediction by the Environmental Protection Agency Toxicity Estimation Software Tool, these compounds exert developmental toxicity. In addition, a nitrogen-containing compound, likely tributylamine (a known lung irritant), was identified based on the molecular weight. This compound has not been previously identified in ENDS e-liquids and aerosols. ENDS produce not only small toxic compounds such as aldehydes, but also large complex toxic compounds such as NIC-PG. Predicted development toxicity for NIC-PG is concerning for fetal development in pregnant women who use ENDS, children exposed to secondhand or thirdhand ENDS aerosols, and teenage ENDS users whose brains are still developing. The strong positive association between NIC-PG levels and ENDS power output supports regulating high-powered ENDS.